Sosialisasi dan Pemahaman Layanan Pinjaman Online bagi Siswa SMA N 2 Mandau - Walhidayat; Sadar, M; Novendra, Rizki; Anugrah, Tjik Dipo (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
The online loan service socialization activity for students at SMA N 2 Mandau, involving 20 twelfth-grade students, aimed to enhance financial literacy, particularly in understanding the benefits and risks of online loan services. Organized by lecturers from the Faculty of Computer Science at Universitas Lancang Kuning, this activity emphasized the importance of using financial services wisely and responsibly. Through presentations, interactive discussions, and case studies, students showed significant improvement in their understanding, as evidenced by survey results indicating an average increase of 30% in comprehension and 40% in risk awareness after the activity. This initiative successfully provided in-depth and relevant education while also raising awareness about financial literacy among the younger generation. The full support from Universitas Lancang Kuning, along with the active participation of students and school staff, was key to the success of this activity.